CTLA-4 CT60 (rs3087243) polymorphism and autoimmune thyroid diseases susceptibility: a comprehensive meta-analysis. (November 2014) - Ni, Jing; Qiu, Li-Juan; Zhang, Min; Wen, Peng-Fei; Ye, Xiao-Ran; Liang, Yan; Pan, Hai-Feng; Ye, Dong-Qing
Abstract Objective: To determine whether the cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) CT60 polymorphism (rs3087243) confers susceptibility to autoimmune thyroid disease (AITDs). Methods: A meta-analysis was performed using: (1) allelic contrast, (2) recessive model and (3) dominant model. Electronic search of PubMed, Medline and Chinese National Knowledge Infrastructure (CNKI) was conducted to select studies. Results: Finally, a total of 20 separate studies were available for the current meta-analysis: Graves' disease (GD): 18 studies including 1 Iranian, 6 Caucasian and 11 Asian populations; Hashimoto's thyroiditis (HT): seven studies including one Iranian, three Caucasian and three Asian populations. A significant association was found between the CTLA-4 CT60 polymorphism (rs3087243) and GD, with regard to comparisons between allele and genotype frequencies (all p < 0.001). After stratification by ethnicity, significant relationships were consistently identified both in Caucasian and Asian populations. Furthermore, the association between this allelic variant and HT risk was also found in overall and Asian populations (OR: 1.26, 95% CI: 1.10–1.44; OR: 1.45, 95% CI: 1.19–1.76, respectively). Conclusion: Taken together, our study suggested that the CT60 polymorphism (rs3087243) in CTLA-4 gene might confer susceptibility to the AITDs (GD/HT).